Pengaruh Durasi Penyimpanan Terhadap Karakteristik Frozen Pulp Kakao - Hajizah, Rihul Jannah; Warkoyo, Warkoyo; Siskawardani, Devi Dwi (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2024)
Cocoa pulp is a substrate rich in albuminoid nutrients which can be used in industrial processes to produce by-products in the form of frozen cocoa pulp. The shelf life must be determined to ensure that frozen cocoa pulp products are high quality. This study aimed to determine the effect of frozen cocoa pulp storage duration on the characteristics of the materials used and to determine the best treatment for the quality of frozen cocoa pulp. The research design used was a Completely Randomized Design with four storage length treatments, namely (0 hours, 2 hours, 4 hours, and 6 hours), with each treatment repeated thrice. Each data obtained was processed using analysis of variance at α = 5%. If it has a significant effect, the data is further tested using the DMRT (Duncan's Multiple Range Test). Parameters observed in cocoa pulp were pH, temperature, color intensity, and organoleptic (aroma, taste, and color). The research results showed that the pH value in cocoa pulp was around 3-3.4 after the sterilization process and it was stated that the acidity level began to change after 4 hours of treatment. The effect of temperature on the sample also affects changes in the shelf life components of cocoa pulp. The color intensity level test on the sample has a relatively darker color after the sterilization process. In the organoleptic test, the highest level of preference was obtained from each treatment's aroma, taste, and color test, namely for a duration of 0-4 hours.